Challenges of the Common Foreign and Security Policy of the European Union after Russia-Ukraine War - Gorgiladze, Marita (Teisė, 2024)
The outbreak of the Russia-Ukraine war marked a geopolitical awakening for the EU. It prompted a reevaluation of EU foreign and security policies, revealing shortcomings in direction and cohesion. The EU reacted to Russia‘s war of aggression against Ukraine, which began on February 24, 2022, by imposing severe and unprecedented sanctions against it. The economic penalties are intended to hold Russia accountable for its conduct and to successfully obstruct Russian efforts to prolong the attack. Those who support, finance, carry out, or who gain from actions that undermine Ukraine‘s territorial integrity, sovereignty, or independence is the subject of individual sanctions.The CFSP, governed by the Treaty on European Union, is primarily enforced through Council decisions, with Article 29 being a key provision used for adopting foreign policy positions and imposing sanctions. However, the legal nature of CFSP decisions, often considered „soft law,“ presents challenges in their implementation and enforcement. Additionally, the paper discusses the procedural aspects of adopting restrictive measures, highlighting the complexities involved in unanimity among Member States and the subsequent enforcement at the national level.Judicial review of CFSP decisions, particularly in the context of sanctions, is explored through case analyses. The paper examines recent court cases related to CFSP decisions, including challenges to sanctions imposed on individuals and entities. The analysis underscores the difficulties courts face in balancing CFSP objectives with fundamental rights, particularly regarding media regulation and freedom of expression.The paper concludes by emphasizing the need for a more unified and effective CFSP framework, especially in the face of evolving geopolitical challenges. It highlights the importance of addressing the shortcomings in CFSP decision-making processes and ensuring a balanced approach to judicial review to uphold the rule of law and fundamental rights while enhancing the EU‘s external actions‘ legitimacy and efficacy.